Clinical Experience of Activated Recombinant Human Coagulation Factor VII for Intracranial Rehemorrhage in an Infant with Hemophilia A with Inhibitor - TABUCHI, Ken; SEKIDO, Ken-ichi; KIGASAWA, Hisato (The Japanese Journal of Pediatric Hematology, 2002)
A four-month-old male infant with life-threatening intracranial hemorrhage was admitted to the Kanagawa Children's Medical Center and diagnosed with severe hemophilia A (FVIII : C<1%). His intracerebral hematoma was removed immediately under the replacement with recombinant factor VIII (rFVIII), and complete hemostasis was attained. After a month's use of rFVIII concentrate, he acquired the inhibitor to factor VIII exactly when he took cranioplasty. This was followed by serious epidural hematoma. We first tried to overcome the low titer of inhibitor with the use of high-dose rFVIII concentrate. Because his inhibitor became greater than 10 BU/ml, replacement therapy was ineffective. The emergent use of recombinant activated factor VII (rFVIIa, NovoSeven®) led to hemostasis. The adequate dose (90-120μg/kg body weight) of rFVIIa was injected every 2-3 hours ; the flow of bleeding from drainage then stopped completely. The total administration of rFVIIa is 138 mg/body, corresponding to 6.7 mg/kg. One-and-a-half years after the onset, he is not subjected to neurological abnormality related CNS bleeding. We find a strong negative correlation coefficient between FVII activity and PT (prothrombin time) under the continuous use of rFVIIa. There was no adverse event related to rFVIIa therapy containing DIC and thrombosis.